2016
DOI: 10.7448/ias.19.1.20524
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations among HIV controllers and persons with medically controlled HIV in the U.S. Military HIV Natural History Study

Abstract: IntroductionHIV controllers (HICs) experience relatively low-level viraemia and CD4 preservation without antiretroviral therapy (ART), but also immune activation that may predispose to adverse clinical events such as cardiovascular disease and hospitalization. The objective of this study was to characterize the rates and reasons for hospitalization among HICs and persons with medically controlled HIV.MethodsSubjects with consistently well-controlled HIV were identified in the U.S. Military HIV Natural History … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 34 publications
0
52
0
Order By: Relevance
“…Likewise, Pereyra et al [ 20 ] reported that elite controllers had increased coronary and immune activation. By contrast, in younger population (median age 27 years) such higher rate of cardiovascular hospitalization rates were not observed [ 21 ]. We found no association between the baseline CD4/CD8 ratio and loss of HIC status, whereas HIV RNA values 50–500 cp/mL were associated with a 5.5-fold higher risk of progression compared to ≤50 cp/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Pereyra et al [ 20 ] reported that elite controllers had increased coronary and immune activation. By contrast, in younger population (median age 27 years) such higher rate of cardiovascular hospitalization rates were not observed [ 21 ]. We found no association between the baseline CD4/CD8 ratio and loss of HIC status, whereas HIV RNA values 50–500 cp/mL were associated with a 5.5-fold higher risk of progression compared to ≤50 cp/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have not been consistent in demonstrating the primary diagnoses that drive inpatient utilization. One cohort study of HIV-infected military personnel between 2000 and 2013 found that non-AIDS-defining infections were the most common cause of hospital admission [ 16 ]. Other studies suggest that AID-related diagnoses, non-AIDS-related cancers, and liver disease account for the majority of deaths in HIV-infected persons during a similar time period [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human immunodeficiency virus/HCV coinfection carries morbidity and mortality risks independent of liver disease, and it is associated with a higher risk of insulin resistance, diabetes mellitus, and renal disease than HIV infection alone [ 14 , 15 ]. Studies examining HIV-infected and HIV/HCV-coinfected patients suggest that these nonliver-related comorbidities, as well as psychiatric/substance use disorders and non-acquired immune deficiency syndrome (AIDS)-associated infections, may be major contributors to healthcare utilization (HCU) [ 16 18 ].…”
mentioning
confidence: 99%
“…Some studies have analysed the risk of nADEs in different cohorts of controllers (27)(28)(29)(30)(31)(32) (summarized in Table 1). Crowell et al studied 149 "elite" controllers and reported that they were at a greater risk of all-cause hospitalizations (especially, hospitalizations for psychiatric and cardiovascular diseases), relative to PLWH on ART (29).…”
Section: What Is the Justification For Treating Controllers?mentioning
confidence: 99%